Effects of Netrin-1 and NHE1 Participation on the Migration of Macrophages Driven by CCL2: Netrin-1 and NHE1 effects on the Migration of Macrophages - Zhang, Shiyue; Mo, Xiangang; Zhang, Shuping; Chen, Juhai; Wang, Lan; Yang, Hui (Cellular and Molecular Biology, 2022)
This experiment was designed to investigate the relationship between NHE1 gene expression differences between Netrin-1 and NHE1. For this purpose, the blank control, CCL2, CCL2 + Netrin-1 groups were constructed, and cell migration ability was detected by scratch tests and Transwell experiments; Commercial over-expressed NHE1 adenovirus vector (over-expressed NHE1 group), shRNA adenoviral vector silencing NHE1 (silencing NHE1 group) and negative control without carrying virus (negative control group) were subjected to RT-PCR test 24h after infection and pH recovery rate after acid loading was measured. The percentage of wound healing area and the number of cell migration of macrophages in the blank control group, CCL2 group, CCL2+Netrin-1 group, over-expressed NHE1 group, silencing NHE1 group and negative control group were compared. Results showed that in terms of migration ability, the percentage of wound healing area and migration in CCL2 increased (P <0.05), in CCL2 + Netrin-1 (P <0.05) and increased NHE1 mRNA (P <0.05), and not in NHE1 (P <0.05).pH response rate after acid load (NHE1 activity) showed that NHE1 activity was enhanced compared with the blank group, while NHE1 activity in silent NHE1 group decreased (P <0.05); from macrophage migration ability after overexpression/silencing, the percentage of macrophage wound healing area and cell migration increased/decreased compared with CCL2 group and Netrin-1 + CCL2 group (P <0.05). Then Upregulation of NHE1 can promote CCL2-driven macrophage RAW264.7 cell migration, and the downregulation of NHE1 can inhibit its cell migration; Netrin-1 can inhibit CCL2-driven RAW264.7 cell migration regardless of NHE1 regulation.